Economic and legal aspects of EU insurance market development. - Havrylyuk, Ruslana (My University, 2021)
Background: Differences related to the development of the insurance market in the EU countries have led to the development and implementation of a regulatory environment through the implementation of the relevant Directives of the European Parliament and the Council of the European Union. Such legal changes provide for the unification of requirements for the activities of insurance companies and are aimed at improving the conditions for the development of the EU internal insurance market. The purpose of the study: to study the main indicators of the EU insurance market and to assess the measures taken by EU member states to transpose the requirements of regulatory directives into national law. Methods: quantitative and qualitative analysis; synthesis; system approach; content analysis; prognostication; trend models. Results: The EU insurance market is the largest segment of the global insurance market. In terms of insurance premiums in most EU countries, the insurance business tends to grow. In 2018, almost 7,000 both national and foreign insurance companies operated in the EU market. It was found that the number of relevant regulatory measures to transpose the requirements of Directive 2009/138 / EU Solvency II was higher in those EU countries where the insurance market is less developed, i.e. their legislation did not meet the generally accepted requirements. The existing regulatory regime of the EU countries has led to differences in approaches to the transposition by national authorities of the requirements of Insurance Distribution Directive 2016/97 / EU. The results of forecasting based on the trend model show that the insurance market tends to grow, as the positive impact of changes in the legal regulation of EU member states will have a lasting effect.
Keywords: Insurance regulation in the EU; The effectiveness of Solvency II; EU insurance markets; Legal regulation of the insurance market